Joke Strategies in American Situational Comedy "How I Met Your Mother" - Awliya Rahmi (JURNAL ARBITRER, 2017)
The research discusse joke strategies in American situational comedy How I Met You Mother (HIMYM). The purpose of this research is to identify; (1) the joke strategies in situational comedy HIMYM (2) The pragmatic meaning of jokes that are expressed by the characters in HIMYM AND (3) Pragmatic prank functions that are expressed by the characters in HIMYM. This research is categorized as descriptive linguistic research. Observation method applied in data collection, while the method of distribution and matching applied in analyzing data. The results of this research data analysis is presented using informal and formal methods. From the results of data analysis found 14 strategy joke uttered by characters in a situational comedy American HIMYM, namely: ambiguity, grammar, syllabics, idiomatics, questionable English, antonymics, style, negativism, lexicography, spelling, punctuation, Rhyming English, numerical English And part of speech. The dominant strategy used is ambiguity because there are many words in English that mean more than one and are likely to lead the listener to multiple interpretations. The jokes uttered by the characters in situational comedy HIMYM have assertive, expressive and directive meanings. Moreover, the joke also serves to show the power, solidarity and psychological defense of the speaker.